Archaeological site types, and assemblage size and diversity in Aotearoa New Zealand. Issue 2 (11th March 2022) - Phillipps, Rebecca; Holdaway, Simon; Barrett, Matthew; Emmitt, Joshua
Abstract: Archaeological settlement models involve the identification of functional site types like base camps and extraction sites based, in part, on differences in the range and frequency of artefact types and fauna. Using reports describing such assemblages from Aotearoa (New Zealand) archaeological sites dating to the first 300 years after initial colonisation, differences in assemblage composition are assessed against total assemblage size. Aotearoa provides a particularly useful test case for the archaeological identification of site types since human colonisation was relatively late in world human history meaning that assemblage accumulation should show functional site types like those identified in the ethnographic record. To test this, SHE (Richness, Heterogeneity, Evenness) diversity analysis is used to examine 18 artefact and ten faunal assemblages dated pre‐1500 CE from a variety of Aotearoa locations. Results suggest artefact and faunal diversity measures perform poorly when employed to differentiate functional site types, suggesting that the null hypothesis of assemblage size dependency cannot be rejected. This result allows for comment on the appropriateness of ethnographically derived functional site types for the study of the archaeological record even when this record accumulated over short time periods. Résumé: Les modèles de peuplement archéologique impliquent l'identification de types de sites fonctionnels tels que les camps de base et les sites d'extraction en se basant, en partie, sur les différences dans la gamme et la fréquence des types d'artefacts et la faune. À l'aide de rapports décrivant de tels assemblages provenant de sites archéologiques d'Aotearoa (Nouvelle‐Zélande) datant des 300 premières années après la colonisation initiale, les différences de composition des assemblages sont évaluées par rapport à la taille totale de l'assemblage. Aotearoa fournit un cas test particulièrement utile pour l'identification archéologique des types de sites puisque la colonisation humaine était relativement tardive dans l'histoire humaine mondiale, ce qui signifie que l'accumulation d'assemblages devrait montrer des types de sites fonctionnels comme ceux identifiés dans les archives ethnographiques. Pour tester cela, l'analyse de la diversité SHE (Richness, Heterogeneity, Evenness) est utilisée pour examiner 18 artefacts et 10 assemblages fauniques datés d'avant 1500 CE provenant de divers emplacements d'Aotearoa. Les résultats suggèrent que les mesures de la diversité des artefacts et de la faune fonctionnent mal lorsqu'elles sont utilisées pour différencier les types de sites fonctionnels, suggérant que l'hypothèse nulle de la dépendance de la taille de l'assemblage ne peut pas être rejetée. Ce résultat permet de commenter la pertinence des types de sites fonctionnels dérivés de l'ethnographie pour l'étude du dossier archéologique, même lorsque ce dossier s'est accumulé sur de courtes périodes de temps.